GC-MS, FTIR and Antiulcer Screening of Aqueous Seed Extract and Oil of Nigella sativa in Wistar Rats - Bruce, S.O.; Nwafor, O.I.; Omoirri, M.A.; Adione, N.M.; Onyeka, I.P.; Ezeoru, V.C. (Journal of Drug Delivery and Therapeutics, 2021)
Peptic ulcer disease (PUD) is a sore in the lining of the stomach or duodenal mucosa. This study was aimed at evaluating the antiulcer activity of the aqueous extract of Nigella sativa (black seed) and its constitutents. The pharmacognostic properties of the dry seeds were determined. The seeds were extracted using two methods digestion and hydro-distillation. The acute toxicity, phytochemical constituents and the antiulcer evaluation were performed on ethanol-induced ulcer in wistar rats using a standard method. FTIR and GC-MS analysis of the aqueous seed extract was also determined using standard methods. Nigella sativa seed shows the presence of starch grains, lignified tissues, tannins, cellulose, protein and oil globules. The aqueous extract has a high safety margin. The phytochemical studies revealed the presence of saponins, flavonoids, alkaloids, tannins, glycosides, fats and oil. The black seed aqueous and oil extract at 500 mg/kg significantly reduced the acidity, total acidity, and ulcer index, and pH of gastric content when compared with the positive control (Famotidine). The FTIR analysis identified the presence of the following functional groups chloro, ether, amine, carboxylic acid, nitriles, methylene, alcohol, while the GC-MS identified five compounds such as glycerin, n-Hexadecanoic acid, 9, 12-octadecadienoic acid-methyl ester, 9, 12-octadecadienoic acid and 9, 12-octadecadienoyl chloride. The pharmacognostic properties can act as a reliable tool for the standardization of the plant part. This study suggests that aqueous and oil extract possess antiulcer properties. Thus the aqueous and oil extract of black seed can be considered as antiulcer medication traditionally. Keywords: Nigella sativa, Black seed, Pharmacognostic, Phytochemical, Acute toxicity (LD50), Antiulcer.